Theorizing Foreign Policy in a Globalized World - Hellmann, Gunther.; Hellmann, Gunther.; Jørgensen, Knud Erik.; Jørgensen, Knud Erik. (Palgrave Studies in International Relations, 2015)
In this collection of refreshing and provocative essays, the contributors to Theorizing Foreign Policy in a Globalized World reflect on the game-changing political impact of globalization, outlining the situation as it currently stands and suggesting strategies for analyzing foreign policy and global governance.